Current concepts and practical techniques of nerve-sparing laparoscopic radical hysterectomy. (December 2016) - Kyo, Satoru; Kato, Tomoyasu; Nakayama, Kentaro
Abstract: Laparoscopic radical hysterectomy has been widely performed for patients with early-stage cervical cancer. The operative techniques for nerve-sparing to avoid bladder dysfunction have been established during the past three decades in abdominal radical hysterectomy, but how these techniques can be applied to laparoscopic surgery has not been fully discussed. Prolonged operation time or decreased radicality due to less accessibility via a limited number of trocars may be a disadvantage of the laparoscopic approach, but the magnified visual field in laparoscopy may enable fine manipulation, especially for preserving autonomic nerve tracts. The present review article introduces the practical techniques for sparing bladder branches of pelvic nerves in laparoscopic radical hysterectomy based on understanding of the pelvic anatomy, clearly focusing on the differences from the techniques in abdominal hysterectomy.